Towards Green Innovation by China’s Industrial Policy: Evidence From Made in China 2025 - Xu, Lanxiang (Frontiers in Environmental Science, 2022)
Government policy is an effective strategy to encourage green innovation, but the effect of industrial policy on enterprise green innovation remains under-explored. Using China’s listed manufacturing enterprises data from 2010 to 2020, this paper employs Made in China 2025 as a quasi-natural experiment as well as the DID method to explore the effect and mechanism of industrial policies on GI. The following key insights are obtained. (i) The Made in China 2025 has the potential to substantially improve the green innovation of manufacturing enterprises. This result shows that industrial policy can promote green innovation to boost the green transformation and upgrading of China's manufacturing industry. (ii) The policy effect is largely dependent on enterprise governance and regions. (iii) Further mechanism considerations find that Made in China 2025 promotes green innovation through tax, environmental subsidies, and corporate social responsibility. In addition to enriching the literature on industrial policy and green innovation, this paper offers valuable implications for government green governance and enterprise's green transformation. Several suggestions for the implementation of Made in China 2025 are proposed.